2021
DOI: 10.1038/s41598-021-87638-5
|View full text |Cite
|
Sign up to set email alerts
|

Diamond formation from methane hydrate under the internal conditions of giant icy planets

Abstract: Hydrocarbon chemistry in the C–O–H system at high pressure and high temperature is important for modelling the internal structure and evolution of giant icy planets, such as Uranus and Neptune, as their interiors are thought to be mainly composed of water and methane. In particular, the formation of diamond from the simplest hydrocarbon, i.e., methane, under the internal conditions of these planets has been discussed for nearly 40 years. Here, we demonstrate the formation of diamond from methane hydrate up to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 38 publications
4
11
0
Order By: Relevance
“…As shown in Fig. 6, the diamond formation observed in our experiments (Kadobayashi et al 2021) occurred under milder conditions than those previously reported. Wentorf (1965) reported that the conditions of diamond formation depend significantly on the composition of the initial hydrocarbon material.…”
Section: Significance Of Mh Stability In Planetary Sciencesupporting
confidence: 66%
See 4 more Smart Citations
“…As shown in Fig. 6, the diamond formation observed in our experiments (Kadobayashi et al 2021) occurred under milder conditions than those previously reported. Wentorf (1965) reported that the conditions of diamond formation depend significantly on the composition of the initial hydrocarbon material.…”
Section: Significance Of Mh Stability In Planetary Sciencesupporting
confidence: 66%
“…Moreover, octahedral-shaped diamond particles were observed in the recovered sample quenched under ambient temperature and pressure conditions, and Raman spectroscopy revealed a characteristic Raman peak for the diamonds at 1331 cm −1 . The presence of hydrogen molecules was also observed in the sample chamber (Kadobayashi et al 2021). Although several experimental reports on diamond formation have been published (e.g., Zerr et al 2006;Kraus et al 2017), our in situ XRD, Raman spectroscopy, and SEM observations and recovered sample data provide unambiguous evidence for diamond formation based on theoretical prediction made 40 years ago (Ross 1981).…”
Section: Significance Of Mh Stability In Planetary Sciencesupporting
confidence: 66%
See 3 more Smart Citations